Detection of genuine grass pollen sensitization in children by skin testing with a recombinant grass pollen hybrid. Issue 1 (25th November 2018) - Douladiris, Nikolaos; Garib, Victoria; Focke‐Tejkl, Margit; Valenta, Rudolf; Papadopoulos, Nikolaos G.; Linhart, Birgit
Abstract: Background: Skin testing represents a commonly used first diagnostic method in clinical practice, but allergen extracts may vary in composition and often contain cross‐reactive allergens and therefore do not always allow the precise identification of the sensitizing allergen source. Our aim was to investigate the suitability of a single recombinant hybrid molecule, consisting of the four major timothy grass pollen allergens (Phl p 1, Phl p 2, Phl p 5, and Phl p 6) for in vivo diagnosis of genuine grass pollen allergy in children suffering from pollinosis. Methods: Sixty‐four children aged from 6 to 17 years with a positive skin reaction and/or specific IgE to grass pollen extract and respiratory symptoms of pollinosis as well as 9 control children with allergy to other allergen sources were studied. SPT was performed with the recombinant hybrid, the four recombinant timothy grass pollen allergens, and grass pollen extract. Specific IgE reactivity to 176 micro‐arrayed allergen molecules was determined using ImmunoCAP ISAC technology. IgE reactivity to the hybrid was detected by non‐denaturing RAST‐based dot blot assay. Results: Genuine grass pollen sensitization was confirmed in 94% of the children with positive SPT to grass pollen extract by SPT and IgE reactivity to the hybrid. The four hybrid‐negative children showed IgE reactivity to cross‐reactive allergens such as Phl p 4, Phl p 11, and Phl p 12 and had also sensitizations to pollen allergens from unrelated plants. Conclusions: The recombinant hybrid molecule represents a useful tool for in vivo diagnosis of genuine grass pollen sensitization.